THE POTENTIAL INDUSTRY OF ISLAMIC TOURISM IN SOUTHEAST ASIAN (SEA) COUNTRIES - Nurrachmi, Rininta (UNISSULA, 2019)
Southeast Asian (SEA) countries is rich with natural resources and historical heritage. The high number of Muslim populations in SEA countries can be a potential revenue to promote Islamic tourism. This study aimed to examine the potential of Islamic tourism industry as alternative revenue and it seeks to investigate the effective and efficient way to promote Islamic tourism in SEA. There are many potential factors that promote Islamic tourism in SEA countries. Push and pull factors influence Muslim tourists is deciding which place they want to visit. Collaboration and coordination among SEA countries can enhance Islamic tourism the developing of Islamic tourism in the region eventually economic benefit can be gained to enhance the countries’ revenue.